Attitude is the key to self-employment : analysis of student’s attitudes towards self-employment using the Theory of Planned Behavior - Tretten, Phillip (2005)
The purpose of this thesis was to explore the role of attitudinal obstacles and facilitators of the students at Luleå University of Technology to becoming self-employed. This was conducted through Icek Ajzen’s theory of planned behavior which measures behavioral antecedents: intentions, attitudes, norms and control and their belief constructs. The survey contained 1384 respondents, of which 979 answered a web-based questionnaire and 405 answered a paper-based questionnaire. The survey was conducted from March 5 to April 4, 2004. Both questionnaires were conducted on the student’s free-time where as the paper-based questionnaire approached the students in the classroom did the web-based questionnaire get sought out by the students online. The SPSS statistical program was used to calculate frequencies, mean values and standard deviations. Differences were tested with chi-square test. Many students showed a positive intention, a positive attitude, and a high level of control over becoming self-employed. They also believed that they would not receive much social support if they were to become self-employed. The students showed that they were not willing to become self-employed at the present time even if they had future intentions to. The underlying reasons to this unwillingness were the lack of creativity which presented itself in the lack of ideas, lack of knowledge and fear of unknowns. The driving factor to why both female and male students saw self-employment as a viable option was the ability to self-realization. Males placed substantially more importance on income. The paper-based students had the least amount of experience in self-employment and were the most interested in learning about self- employment. Four hinders to self-employment have been made manifest: lack of interest to change, lack of social support, lack of desire to change, and the incapacity of becoming self-employed. All four of factors are rooted in the students’ lack of correct knowledge about being an entrepreneur. The entrepreneurial ...